Thermolysis of medical plastic wastes using Zeolite A catalyst-kinetic study, experimental optimisation and validation - Das, Amar Kumar; Rout, Saroj Kumar; Panda, Achyut Kumar (Journal of Environmental Engineering and Landscape Management, 2022)
This work reports the thermo-catalytic conversion of medical plastic wastes to fuel oil using the detergent grade Zeolite A as the catalyst. The effect of catalyst on the pyrolysis is ascertained from the kinetic data obtained from thermogravimetric analysis assuming it to be a first-order reaction. A significant reduction in activation energy of the thermal degradation reaction is found in presence of the Zeolite A catalyst. The pyrolysis runs were performed at different temperatures from 400–550 °C in a stainless-steel batch reactor system to obtain an optimum condition for suitable waste to energy process. The highest oil yield of 79% was obtained at 500 °C with 10% catalyst concentration. The thermogravimetric analysis and the batch pyrolysis experimental result indicated a promising effect of the catalyst in terms of the enhanced rate of reaction and conversion. The oil fraction obtained in the optimum condition of catalytic pyrolysis was analysed for its composition and fuel properties. It confirmed the presence of branched alkane and alkene with composition C10–C18. Again, the fuel properties of the oil such as specific gravity (0.793), viscosity (3.75Cst@ 30 °C), and flash point (<11 °C) resemble that of the petro fuels. Neural Networks (NNs) are used to recognize patterns, and relationships in data and validate the experimental results of this reaction and the results indicate that the use of ANN in thermo-catalytic degradation of medical waste to fuel oil is a feasible option that should be considered for real-time applications.